Find the inverse of g(n) = – 3 – 1 Og-1 (n) = -(n-3)-1 9 9-1 (n) = In g-1 (n) = (n + 1)3 + 3 Og-1 (n) = 3+n3<

Question

Find the inverse of g(n) = – 3 – 1
Og-1 (n) = -(n-3)-1
9
9-1 (n) = In
g-1 (n) = (n + 1)3 + 3
Og-1 (n) = 3+n3

in progress 0
bonexptip 1 year 2021-09-05T07:58:43+00:00 1 Answers 4 views 0

Answers ( )

    0
    2021-09-05T07:59:46+00:00

    Answer:

    [tex]g'(n) = -\frac{n+1}{3}[/tex]

    Step-by-step explanation:

    Given

    [tex]g(n) = -3n – 1[/tex]

    Required

    Determine the inverse

    [tex]g(n) = -3n – 1[/tex]

    Replace g(n) with y

    [tex]y = -3n – 1[/tex]

    Swap positions of x and y

    [tex]n = -3y – 1[/tex]

    Make y the subject

    [tex]3y = -n – 1[/tex]

    [tex]3y = -(n + 1)[/tex]

    [tex]y = -\frac{n+1}{3}[/tex]

    Replace y with g'(n)

    [tex]g'(n) = -\frac{n+1}{3}[/tex]

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )